To Build or Not to Build - Tieman, Rob; Berne, Rosalyn (University of Virginia, 2025)
There are times when what appears to be a straightforward engineering project is actually replete with nodes of ethical concern that might easily be overlooked. Such is so with this (fictional) case of planning for the construction of a new road in western Washington State.
Original submission date: 2025-10-29T16:56:18Z
Keywords: Civil and Environmental Engineering; Public Engagement; Animal Well-Being; Responsible Innovation; Ethics; Climate; Engineer/Client Relationships